A convenient strategy for the electrochemical evaluation of acetaminophen and caffeine in combined drugs and biological samples over TiO2@polymethyldopa/Pd nanocomposite functionalized glassy carbon electrodes. (December 2021) - Lotfi, Shahram; Veisi, Hojat; Karmakar, Bikash
Graphical abstract: Highlights: The TiO2 /PMDA/Pd/GCE sensor was suggested for simultaneous measurement of AC and CF. The TiO2 /PMDA/Pd/GCE sensor showed electrocatalytic activities towards the electro oxidation of AC and CF. The application was performed for human blood serum and commercial tablet samples. Abstract: In this study, a sensitive electrochemical sensor was designed based on Pd nanoparticles adorned poly-methyldopa (PMDA) modified TiO2 nanoparticles embedded over glassy carbon electrode (TiO2 @PMDA/Pd/GCE) for the simultaneous quantitative estimation of acetaminophen (AC) and caffeine (CF) in biological and pharmaceutical samples. Several analytical techniques like Fourier Transformed Infrared spectroscopy (FT-IR), Field Emission Scanning Electron Microscope (FE-SEM), Transmission Electron Microscopy (TEM) and Energy Dispersive X-ray Spectroscopy (EDX) were used to characterize the as synthesized nanocomposite. Electrochemical properties of the constructed sensor were evaluated using cyclic voltammetry (CV). Following the optimization of some experimental parameters in differential pulse voltammetry (DPV), the anodic peak currents for both the molecules were found to be linear with their corresponding concentrations ranging from 5 nM to 3.5 µM and 50 nM to 4.5 µM respectively. Detection limits for AC and CF molecules were being 1.94 nM and 23.9 nM in this estimation. The fabricated sensor was advantageous in terms of ease of preparation, great stability, excellent selectivity, repeatability and reproducibility. To evaluate of electrode-to-electrode reproducibility the relative standard deviation (RSD%) were obtained to be 3.6% for AC and 4.5% for CF, respectively. The precision was measured to be below 4.3% for AC and 3.9 for CF, and accuracy between −1.7% − 3.5% for AC, and −3.7–2.5 for CF, respectively. Statistical student's t -test and F-test displayed negligible systematic error between the measured and real values and also between voltammetric method at the surface of the suggested electrode and standard HPLC method.